Oxime-derived palladacycles bearing 2,6-lutidine: Synthesis, cytotoxicity evaluation and interactions with biomolecules - Polez, Ana M.R. [UNESP]; Farias, Renan L. [UNESP]; de Lima, Andresa A. [UNESP]; Lazzarini, Ana Beatriz [UNESP]; de Moura, Thales R. [UNESP]; Velasques, Jecika M. [UNESP]; Souza, Jessica Carolina [UNESP]; Rocha, Fillipe V.; Lima, Mauro Almeida; Ellena, Javier; Miranda, Victor Maia; Deflon, Victor M.; et al. (Elsevier, 2025)
In this study, we report the synthesis, characterization and biological studies on new organometallic compounds bearing orthopalladated oximes and 2,6-lutidine. Cyclopalladated compounds of the type [PdCl(C2,N-ox)(lut)] {ox: bzox = benzaldehydeoxime (1), aphox = acetophenoneoxime (2), tetrox = E-α-tetralone oxime (3); lut = 2,6-lutidine} have been obtained from the reaction between the suitable [Pd(C2,N-ox)(µ-Cl)]2 precursor with 2,6-lutidine. The compounds have been characterized by elemental analyses, infrared (IR) and NMR spectroscopies. The molecular and crystal structures of 1 – 3 have been determined by single-crystal X-ray crystallography. The cytotoxic activity of compounds 1–3 has been evaluated towards breast (MCF-7 and MD-MBA-231) and lung (A549) human cancer cells along with human lung fibroblast (MRC-5). The level of cytotoxicity is dependent on the tested tumour cell line and the type of orthometallated oxime. The binding properties of the model compound 3 on ct-DNA have been studied using UV–Vis titration, circular dichroism and fluorescence spectroscopy.
Keywords: Cancer; Cyclopalladated complex; DNA; Oximes